2004
DOI: 10.1021/cg049763e
|View full text |Cite
|
Sign up to set email alerts
|

SHG Active Salts of 4-Nitrophenolate with H-Bonded Helical Formations:  Structure-Directing Role of ortho-Aminopyridines

Abstract: Among the several approaches developed for the fabrication of molecular crystals with noncentrosymmetric lattices, incorporation of chirality is the only one which guarantees it for fundamental symmetry reasons. One of the few quadratic nonlinear optical chromophores which form a large number of noncentric cocrystals/salts without the assistance of chirality is 4-nitrophenolate; hence it is an ideal candidate to explore new avenues to noncentric lattice formation. The utility of a structure-directing counterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…The SHG efficiency of the grown crystal was 11.5 times (the insert in Fig. 6) that of urea (close to the data reported by literature [20]). Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The SHG efficiency of the grown crystal was 11.5 times (the insert in Fig. 6) that of urea (close to the data reported by literature [20]). Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, organic molecular crystals show a strong predilection toward centrosymmetric organization structure. In the past decades, many approaches have been developed to acquire noncentrosymmetric crystals [17][18][19][20] in which one way to include both ionic and hydrogen-bonding interactions in a system is to form ionic co-crystals from proton transfer between an organic acid and organic base [21][22][23]. 4-nitrophenolate (NP-) with a typical one-dimensional (1D) donor-acceptor p system and the proton transfer of phenolic OH with various organic and inorganic bases results in the increasing of hyperpolarizability of both species has been used to form a large number of noncentrosymmetric structures with the achiral counterions [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present communication continues the previous investigations and is devoted to the study of relationship between the composition and some properties of aminopyridinium hexafluorosilicates. Both 2-aminopyridine and 2,6-diaminopyridine are very popular co-crystal formers in supramolecular chemistry of anions [17,18]. In contrast to para-aminopyridine, it is found that ortho-aminopyridines (2-aminopyridine and 2,6-diaminopyridine) support bent pathways of supramolecular assembly through Hbond formation as the amino and pyridinium groups together form a kind of ''angle joint'' [17] and serve as an efficient molecular tecton for the intermolecular assembly supported by hydrogen bonding and in some cases can lead to noncentric cocrystalline salts.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these components resulted in strong hydrogen bonding and the proton transfer that increases the molecular hyperpolarizability [19][20][21]. In the 4-nitrophenol molecule the phenolic group exhibits amphoteric properties acting as hydrogen-bond donor through the hydroxyl H-atom, and electron-donor as well through the oxygen atom lone pair, while the nitro-group is displaying the electron-and hydrogen-bond acceptor properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%